2017
DOI: 10.9734/ajob/2017/34241
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Nematicidal Activity of Ethanolic Leaf Extracts of Datura metel, Datura innoxia and Brugmansia suaveolens Against Meloidogyne incognita

Abstract: The present study was aimed to screen the phytochemicals and quantification of alkaloids, phenolic compounds and flavonoids and to evaluate the nematicidal activity of ethanolic leaf extracts of Datura metel, Datura innoxia and Brugmansia suaveolens against Meloidogyne incognita. Phytochemical screening of leaf extracts of D. metel, D. innoxia and B. suaveolens was carried out by qualitative analysis and the results revealed that the presence of bioactive compounds like alkaloids, steroids, flavonoids, terpeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
(19 reference statements)
1
12
1
Order By: Relevance
“…These results were higher than phenolic compounds (70.3 ± 1.1 mg GAE/g) and total flavonoids (34.2 ± 1.3 mg RE/g) found by Bhardwaj, Kumar and Ojha (2016) for the methanolic extract obtained from the leaves of specimens collected in Haryana, India. However, our results were lower than those obtained by Nandakumar et al (2017) for phenolic compounds (3.62 ± 0.0147 mg/g) and flavonoids (4.12 ± 0.0167 mg/g) found in Datura inoxia leaves collected in different regions of India (Orathanadu Village, Thanjavur District and Tamilnadu)…”
Section: Resultscontrasting
confidence: 94%
“…These results were higher than phenolic compounds (70.3 ± 1.1 mg GAE/g) and total flavonoids (34.2 ± 1.3 mg RE/g) found by Bhardwaj, Kumar and Ojha (2016) for the methanolic extract obtained from the leaves of specimens collected in Haryana, India. However, our results were lower than those obtained by Nandakumar et al (2017) for phenolic compounds (3.62 ± 0.0147 mg/g) and flavonoids (4.12 ± 0.0167 mg/g) found in Datura inoxia leaves collected in different regions of India (Orathanadu Village, Thanjavur District and Tamilnadu)…”
Section: Resultscontrasting
confidence: 94%
“…These changes in the soil properties probably negatively affected the growth or multiplication of the nematodes in the French beans. The findings of this research are also in agreement with those of Aiyadurai et al (2018) who suggested that plant parasitic nematodes can be controlled by application of botanicals. Water and nutrition are important vital components in French bean production life and their limited supply or unavailability is one of the major abiotic factors that adversely affect French beans production in many ways.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 91%
“…The atropine content in the leaves in Datura metel was found to be 0.426%, whereas hyoscyamine levels were found to be 0.426% in the seeds and 0.43% in flower [8]. The alkaloid contents of scopolamine and atropine in the entire plant in D. metel increase gradually with the development of various growth stages and becomes most apparent when the plant reaches the end of its reproductive stage [24,25]. However, in the case of D. stramonium, the maximum amounts of alkaloids were found after ten weeks of seed germination, decreasing gradually with the beginning of the generative phase in plants [8,26].…”
Section: Biochemical Composition Of Daturamentioning
confidence: 94%